The effects of marital status and social isolation on adult male homicides in the United States: Evidence from the National Longitudinal Mortality Study - Kposowa, Augustine J. (Journal of quantitative criminology, 1994)
With data from the 1979–1985 Longitudinal Mortality Study, we examine the effects of marital status and social isolation on adult male homicide (ICD-9 Codes E960-E978). Cox proportional hazards models were fitted to a 1979–1981 population cohort of approximately 200,000 adult men and their mortality experiences were followed until 1984–1985. Multivariate hazards regression analysis showed that marital status and social isolation are associated with significantly higher risks of homicide victimization. Controlling for age and other socioeconomic covariates, single persons were 1.9 times, and divorced, separated or widowed persons were 1.7 times, more likely to die from homicide than married persons. Socially isolated persons were 1.6 times more likely to become homicide victims. Other adult males with increased risk of homicide victimization were African Americans and those who lived in the inner city.